Vivien, R., Brun, C., & Sánchez, N. 2020. Lettres inédites à Jean Charles-Brun (1900-1909 - Fouchard, Flavie (Anales de Filología Francesa, 2021)
Reseña de: Vivien, R., Brun, C., & Sánchez, N. 2020. Lettres inédites à Jean Charles-Brun (1900-1909).